2010
DOI: 10.1088/0953-8984/22/8/085004
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and adhesion of the Nb(001)/α-Nb5Si3(001) interface: a first-principles study

Abstract: The density functional calculations have been performed to study the Nb(001) and α-Nb5Si3(001) surfaces as well as the interface properties of Nb(001)/α-Nb5Si3(001). The surface energy of the Nb(001) surface is about 2.25 J m (- 2). The calculated cleavage energies of bulk Nb5Si3 are 5.103 J m (- 2) and 5.787 J m (- 2) along (001) planes with the breaking of Nb-Si and Nb-NbSi bonds, respectively. For the Nb(001)/α-Nb5Si3(001) models, the Nb atoms in the interface region initially belonging to body centered cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
(67 reference statements)
0
11
0
1
Order By: Relevance
“…A study of a Nb (001) /αNb 5 Si 3(001) interface using a first-principles calculation showed that some of the Nb atoms at the interface become a part of Nb 5 Si 3 , and that the Nb–Si bonds at the interface are the likely sites for micro-cracking [ 71 ]. This study reported that the work of adhesion and fracture energy of the Nb (001) /αNb 5 Si 3(001) interface were 4.4 J/m 2 and 33.7 J/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study of a Nb (001) /αNb 5 Si 3(001) interface using a first-principles calculation showed that some of the Nb atoms at the interface become a part of Nb 5 Si 3 , and that the Nb–Si bonds at the interface are the likely sites for micro-cracking [ 71 ]. This study reported that the work of adhesion and fracture energy of the Nb (001) /αNb 5 Si 3(001) interface were 4.4 J/m 2 and 33.7 J/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The former would be expected to affect the strength of the NbeSi bond compared with the NbeNb bond or NbeTM/RM bond. A recent study has shown that NbeSi bonds are weaker than NbeNb bonds [28]. One motivation for the present work was to explore the role of Mo and W on the chemistry of the Nb ss in the presence/ absence of Hf and to compare with the effect of the synergy of Mo, Ta and Hf.…”
Section: Introductionmentioning
confidence: 99%
“…In the a, b and g forms of Nb 5 Si 3 bonding is dominantly covalent. The unit cell of aNb 5 Si 3 consists of atomic layers some of which are more closely packed and others less closely packed [28]. Substitution is possible in Nb and Si atoms in either type of closely packed layers.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the coherent interface approximation [22] is applied to study the interfaces in which the misfit dislocation is ignored. The coherent interfaces have been investigated by many researchers [23][24][25][26][27][28][29][30][31]; whereas, the obtained theoretical work of adhesion is larger than the observed values [32].…”
Section: Introductionmentioning
confidence: 99%